Diagnostic Performance of Commercial Antithrombin Activity Assays: Do We Get What We Expect? - Orlando, Christelle; Drèze, Céline; Evenepoel, Anton; Seneca, Sara; Jochmans, Kristin (Thrombosis and Haemostasis, 2025)
Hereditary antithrombin (AT) deficiency is a rare autosomal dominant disorder that predisposes to the development of recurrent venous thromboembolism (VTE). Diagnosis is based on the measurement of reduced AT activity in plasma. However, not all commercial AT activity assays are equally suited for diagnosis since they differ in sensitivity toward different AT mutations.The aim of this study was to compare the ability of commonly used AT activity assays to diagnose inherited antithrombin deficiency, with a focus on type II AT deficiencies. We used samples from genetically confirmed AT deficient subjects (n = 76) and from patients with request for AT activity measurement for diagnostic purposes (n = 152). AT activity was measured with five commercial assays on three analyzers.All reagent/analyzer combinations showed specificities varying from 87 to 100%, except for 1 assay (56.5% specificity). Diagnostic sensitivity varied widely between assays, from 36.8% to 100%. All reagent–analyzer combinations correctly identified variants causing type I AT deficiencies but only one variant responsible for type II heparin binding site (HBS) deficiency: p.Arg79Cys. For one of the assays, we observed a large difference in sensitivity (82.9 versus 55.3%) toward antithrombin type II HBS variants depending on the coagulation analyzer on which it is performed, suggesting that incubation time of sample and substrate could be a crucial driver of the sensitivity toward variants causing type II antithrombin deficiency. Our results suggest that inherited antithrombin deficiency is probably underestimated and improved diagnostic strategies are mandatory.
Keywords: antithrombin; antithrombin deficiency; diagnostic performance; heparin binding site; thrombophilia